2008
DOI: 10.1243/09544062jmes923
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution for primary resonances of a rotating shaft with stretching non-linearity

Abstract: In this paper, primary resonances of a simply supported rotating shaft with stretching non-linearity are studied. Rotary inertia and gyroscopic effects are included, but shear deformation is neglected. The equations of motion are derived with the aid of Hamilton's principle and then transformed to the complex form. To analyse the primary resonances, the method of multiple scales is directly applied to the partial differential equation of motion. The frequency—response curves are plotted for the first two modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The characteristic of the steady-state amplitude curve of the unbalanced rotor system with weak stiffness is similar to that of the linear unbalanced rotor system when k s is small and the value of the amplitude reaches the peak near the first critical speed. This phenomenon clearly implies that the larger nonlinear stiffness can induce more obvious nonlinear vibration characteristics and balancing the rotating shaft is necessary especially if it operates beyond the first critical speed [18]. In Figure 4b, the nonlinear amplitude curves exhibit a similar twisting property for different ω 0 and the larger ω 0 corresponds to the larger maximum amplitude, which means that the decreasing system natural frequency is beneficial to reducing the vibration amplitude.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The characteristic of the steady-state amplitude curve of the unbalanced rotor system with weak stiffness is similar to that of the linear unbalanced rotor system when k s is small and the value of the amplitude reaches the peak near the first critical speed. This phenomenon clearly implies that the larger nonlinear stiffness can induce more obvious nonlinear vibration characteristics and balancing the rotating shaft is necessary especially if it operates beyond the first critical speed [18]. In Figure 4b, the nonlinear amplitude curves exhibit a similar twisting property for different ω 0 and the larger ω 0 corresponds to the larger maximum amplitude, which means that the decreasing system natural frequency is beneficial to reducing the vibration amplitude.…”
Section: Resultsmentioning
confidence: 89%
“…The numerical results exhibited rich forms of multiperiodic, quasi-periodic and chaotic motion and implied that the nonlinear sealing force had great influence on the dynamic characteristics of the rotor system. Hosseini and Khadem [18] studied the primary resonances of a rotating shaft with stretching nonlinearity and the characteristics of free vibration considering nonlinear inertia and curvature were further analyzed [19]. Vlajic [20,21] studied torsional vibrations of a Jeffcott rotor subjected to the continuous stator contact numerically and analytically for both backward and forward whirling motions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nonlinear analysis of rotating shafts with constant spin was carried out in previous works. [19][20][21][22] The aim of the present study is the investigation of nonstationary motion of rotating shafts with stretching nonlinearity and gyroscopic effect due to the large deformation excited by nonideal energy source. Indeed, combined effect of nonlinearity, gyroscopic effect, and non-ideal energy source is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that prediction of the instability region is different for the linear and nonlinear equations of motion. Hosseini et al [3,4] investigated the nonlinear vibration behavior of rotating shafts with stretching nonlinearity and nonlinearity in curvature and inertia. Łuczko [5] proposed a method for modeling geometrically nonlinear rotating shafts.…”
Section: Introductionmentioning
confidence: 99%